State Guarantees of the Right to Housing for War Veterans: Substantive and Procedural Aspects - Cherneha, Andriy P.; Udovenko, Zhanna V.; Sergiienko, Nataliia A.; Oblovatska, Nataliia O.; Dotsenko, Alyona O. (Cuestiones Políticas, 2020)
The purpose of the article was to reveal the problematic aspects of the realization of the right to housing by war veterans who participated in counter-terrorism operations / joint operations. I am interested in observing the protection of this right in civil, criminal and executive proceedings based on national and international law. The methodological basis of the study includes general and special methods of scientific research (historical, statistical, formal logic, comparative legal and structural logic). Statistics are given on the number of war veterans (combatants) as of 2019-2020, in the dynamics of providing them a living space in Ukraine during 2015-2020. In addition, the article provides examples of the elimination of conflicts of laws and ambiguous judicial practices of application of civil, family, housing and social law, as well as civil, criminal and executive procedure in the field of exercise of the right to housing by combatants and their families, protection of this right before the courts and execution of decisions in this category of cases. The results of this work can be useful for combatants who need to improve their living conditions, as well as for human rights defenders who help these people.